Optimizing transfusion therapy in the chronically transfused patient. (June 2016) - Ang, A. L.
Abstract : Patients may require regular transfusion due to congenital or acquired conditions resulting in haemolysis, ineffective blood cell production, bone marrow failure or a combination of these. In South‐East Asia, the most common congenital cause is thalassaemia while acquired causes include haematological malignancies such as myelodysplastic syndrome (MDS) and acute leukaemia. The major goal of transfusion in these patients is to minimize complications from their conditions. Due to the frequent transfusions, their cumulative risks from transfusion are higher than other patients. The transfusion‐associated adverse events which may affect these patients include mild adverse reactions such as febrile non‐haemolytic transfusion reactions and urticaria, as well as severe complications such as haemolytic transfusion reactions, anaphylaxis, transfusion‐transmitted infections, transfusion‐associated circulatory overload and transfusion‐related acute lung injury (TRALI). In addition, patients who need regular red cell transfusion are at risk of transfusional haemosiderosis. Therefore, measures should be taken to maximize the efficacy of transfusion and minimize the adverse effects of transfusion in these patients.